Gripper Finger Design for Automatic Bottle Opener - Suchada Sitjongsataporn; Kornika Moolpho; Sethakarn Prongnuch (Advances in Science, Technology and Engineering Systems Journal, 2021)
This paper presents a design of parallel gripper finger for robotic dual-arm working with an automatic push-down bottle crown cork cap opener on ABB’s Yumi collaborative bartender robot. A safe gripper finger is made from ABS plastic by 3D printing for human-based interaction design for grasping and holding a glass bottle. Rack design and proposed automatic push-down bottle cap opener using pneumatics are presented to support a gripper finger. Experimental tests as bartender environment with 4-different types of carbonated soft drink with crown cork cap show that can be achieved effectively with average of 91.5% percentage of successful cap opener.
Keywords: Parallel Gripper Finger; Robotic Dual-Arm; Automatic Bottle Opener